Active & reactive powers control of DFIG placed with wind energy system by using hybrid controller - Vasavi Uma Maheswari, M.; P. V. Ramana Rao, Dr.; ., . (International Journal of Engineering and Technology, 2018)
Here paper presents around the Active power along with Reactive power clout of a grid allied doubly fed Induction Generator (DFIG) with wind energy system (WES) employing PI & ANFIS controller. DFIG is formed adapting a d-q revolving allusion cage circuit with stator flux oriented, field oriented clout approach. By using a coterminous converter of Variable speed constant Frequency (VSCF) along with active the reactive power and DC tie voltage are controlled at sub and super synchronous speeds. An ANFIS has been coupled by a conventional PI controller in order to enhance the power controlling capability at steady state and voltage dip conditionsÂ
Keywords: DFIG; WECS; Variable Speed Constant Frequency (VSCF); ANFIS Controller.